PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEOSCRIBE SPARKOL PADA MATERI KEKONGRUENAN DAN KESEBANGUNAN DI SMP PGRI 2 BOGOR - Ardistya Puspita Sari; Indra Martha Rusmana (LPPM Universitas Bina Bangsa, 2021)
This study aims to determine the feasibility of using learning media based on Videoscribe Sparkol on congruence and similarity material at SMP PGRI 2 Bogor. The method used in this study is the Research and Development method using ADDIE development procedures, namely (Analysis, Design, Development, Implementation, and Evaluation). The data collection method used an expert test validation questionnaire. The results of data analysis in the media validation process included media experts, namely 4.00 meaning